EVALUASI PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN: KAJIAN ATAS PELAKSANAAN MUSRENBANG DI JAWA TENGAH - Manar, Dzunuwanus Ghulam (JURNAL ILMU SOSIAL, 2014)
Democratic countries should involve its people into developmental planning. However, it is important to develop legal guide for people in order to participate in developmental process or stages. Indonesia government had established a formula for people and government to work for developmental planning called musrenbang. Some research shows that musrenbang had failed to comply with core principles of democracy that is participation, since it is held dominantly by government. This research will evaluate adn identify implementation of musrenbang based on legal guide and propose some solution in order to solve the problem.